Elaboration and characterization of a battered food, Frozen from earberry (Solanum melongena). - Zalamea Monina, Luis Felipe; García Choez, Luis Agustín; Maldonado López, Jorge David (Ingeniería Química y Desarrollo, 2022)
The main drawback of the eggplant is the rapid oxidation caused by polyphenol oxidase (PPO), comes the need to raise awareness of the different properties that have this vegetable and benefits representing consume, its composition is 92% water, it contains minerals among them we can find abundant potassium, iodine and magnesium also has also has vitamin B1, vitamin C, thiamine, among others and phytonutrient as phytosterols and beta carotene. DPPH analysis of which showed a high content of flavonoids being most stands chlorogenic acid, which helps the removal of free radicals in the body was performed. The limiting factor for the development of this research was the production of this vegetable in Ecuador because they are small and sporadic crops near Canton Daule located in the province of Guayas.